Effectiveness and tolerability of ipilimumab: experiences from 198 patients included in a named-patient program in various daily-practice settings and multiple institutions - Eigentler, Thomas; Schlaak, Max; Hassel, Jessica C.; Loquai, Carmen; Stoffels, Ingo; Gutzmer, Ralf; Pätzold, Sylvie; Mohr, Peter; Keller, Ulrich; Starz, Hans; Ulrich, Jens; Tsianakas, Athanasios; et al. (Journal of immunotherapy, 2014)
Background: - Ipilimumab is an approved anti-cytotoxic T-lymphocyte-associated antigen-4 monoclonal antibody introducing immune responses in melanoma patients. Treatment experiences from named-patient programs support the evaluation of the efficacy and tolerability of new medicines under usual circumstances of health care practice. Here, the largest ever reported cohort treated with ipilimumab 3 mg/kg alone is described. - Methods: - This report retrospectively analyzes data of 198 patients who were followed up in 15 hospital centers in Germany between April 2010 and March 2013. Patients had received prior therapy for unresectable stage III or IV melanoma before receiving ipilimumab (4 doses of 3 mg/kg every 21 d). Routine staging and tumor response evaluation procedures were applied. - Results: - Of the patients, 119 received the planned 4-course therapy schedule; in further 79 patients, the number of doses was reduced mainly because of toxicity or fast progression. In all, 196 patients were eligible for evaluation of the efficacy of ipilimumab under routine care conditions. Median overall survival (OS) was 6.8 months [95% confidence interval, 5.6-10.3] from the start of therapy. OS differed significantly among patients who received 4 doses (n=119) and those receiving <4 doses (n=79) (14.2 vs. 2.0 mo; P<0.0001). The overall response rate (ORR) of 11% was in the same range as reported from previous clinical trials; and stable disease (SD) was observed in 11% resulting in a disease control rate (ORR+SD) of 22%. In 23 of the 79 patients with reduced dosing, dose omission was most probably caused by toxicity, whereas 56 patients had progressive disease before receiving all 4 treatment cycles. Immune-related adverse events (irAE) were reported in 30% of all treated patients, the occurrence of irAE correlated significantly with the probability of response to therapy and prolonged OS. - Conclusion: - In this named-patient program including heavily pretreated patients, the efficacy and tolerability of ipilimumab 3 mg/kg corresponds with findings from the confirmatory clinical trial.